THE BEFORE-AFTER COMPARISON OF PATIENT QUALITY OF LIFE WITH SPLINTING TREATMENT IN DENTAL MOBILITY CASES - Muhammad Husnun Niam; Erna Dwi Agustin; Yogi Pradipta (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Splinting care patients are patients who are to experience by loss of periodontal ligament attachment and bone damage infrabony or suprabony that requires splinting treatment to stabilize the teeth and provide the comfort to the patient. The aim of this research is to find out the differences in life quality before and after splinting treatment in cases of tooth mobility by using the Oral Health Impact Profile Questionnaire - 14.Method: This study uses an observational analytic design with cross sectional design. The sample used total sampling technique that was taken from all splinting care patients at RS/GM Sultan Agung for the period of January-April 2019 in accordance with inclusion criteria of 22 patients. The data were taken from the results of direct and indirect interviews. The data was analyzed using Non-parametric Wilcoxon Signed Ranks Test.Result: Based on the results of data analysis, it showed that there were significant differences (p<0.05) on the results of the data, before and after splinting treatment using the OHIP-14 questionnaire, which means that the splinting treatment using the OHIP-14 questionnaire was changed the life quality of patients in RS/GM Sultan Agung the quality of patients' life become better after splinting treatment.Conclusion: There are differences in patients' life quality before and after splinting treatment.